The Addressing Anxiety Disorder through Indigenous Therapeutics : A Review - Shubhranshul Dwivedi (Dev Sanskriti: Interdisciplinary International Journal, 2022)
In modern times, there is a rise in the number of cases suffering from mental health issues. Anxiety disorder is one of the significant mental illnesses. Various psychological and pharmacological interventions are available to treat anxiety and reduce its symptoms. However, these interventions have various limitations, and comprehensive treatment of this disorder is still a challenge. Ancient indigenous therapeutic techniques such as Yoga Therapy, Marma Therapy and Pranic healing, and Yagya Therapy are promising in the treatment of this disorder. The present study reviewed the applicability of these techniques for the treatment of this disorder. Yoga is an effective therapeutic intervention which can be used to treat anxiety. Yoga helps in addressing the biological symptoms of anxiety disorder. Stimulating marma points helps in mental and physical well-being and the development of self-healing powers. Stimulation of marma points of throat and head helps in treating anxiety disorder. Through pranic healing, the imbalanced chakras responsible for anxiety are energised which influence the physical body, mind, and emotions. Yagya therapy is beneficial in managing anxiety through the fumes of the herbs. It is beneficial in maintaining overall psychological well-being. From the review, it is clear that indigenous therapeutic interventions such as yoga therapy, marma therapy, pranic healing, and Yagya therapy help treat anxiety disorder and maintain good mental wellbeing.